Inheritance pattern of familial moyamoya disease: autosomal dominant mode and genomic imprinting. Issue 9 (20th June 2006) - Mineharu, Y; Takenaka, K; Yamakawa, H; Inoue, K; Ikeda, H; Kikuta, K-I; Takagi, Y; Nozaki, K; Hashimoto, N; Koizumi, A
Abstract : Background: Although the aetiology of moyamoya disease (MMD) has not been fully clarified, genetic analysis of familial MMD (F-MMD) has considerable potential to disclose it. Objective: To determine the inheritance pattern and clinical characteristics of F-MMD to enable precise genetic analyses of the disease. Methods: 15 highly aggregated Japanese families (52 patients; 38 women and 14 men) with three or more affected members were examined. The difference in categories of age at onset (child onset, adult onset and asymptomatic) between paternal and maternal transmission was compared by χ 2 statistics. Results: In all families there had been three or more generations without consanguinity, and all types of transmission, including father-to-son, were observed. Among a total of 135 offspring of affected people, 59 (43.7%) were patients with MMD or obligatory carriers. Affected mothers were more likely to produce late-onset (adult-onset or asymptomatic) female offspring (p = 0.007). Conclusions: The mode of inheritance of F-MMD is autosomal dominant with incomplete penetrance. Thus, in future genetic studies on F-MMD, parametric linkage analyses using large families with an autosomal dominant mode of inheritance are recommended. Genomic imprinting may be associated with the disease.